2020
DOI: 10.1111/1742-6723.13649
|View full text |Cite
|
Sign up to set email alerts
|

Eligibility criteria for extracorporeal cardiopulmonary resuscitation at Auckland City Hospital: A retrospective cohort study

Abstract: Objective: Extracorporeal cardiopulmonary resuscitation (ECPR) is a promising adjunct to routine advanced cardiac life support. Growing worldwide interest in ECPR-use has seen more tertiary centres offering ECPR programmes. New Zealand's nationwide extracorporeal membranous oxygenation service is provided at Auckland City Hospital (ACH). Despite the potential benefits of ECPR, it is currently only offered on an ad hoc basis. It remains unknown whether ACH would manage sufficient numbers of patients to warrant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Iwashita et al . [ 20 ] and Olander et al . [ 26 ] found an ECPR eligibility rate in IHCA patients of 5.5–12.0%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Iwashita et al . [ 20 ] and Olander et al . [ 26 ] found an ECPR eligibility rate in IHCA patients of 5.5–12.0%.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has reported that around 10% of IHCA and 10% of OHCA patients are eligible to ECPR [17–20]. However, the proportion of patients eligible to ECPR in the Netherlands has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The outcome measures evaluated across the studies mainly comprised ROSC (return of spontaneous circulation), survival, neurological outcomes, eligibility for ECPR, and time to extra corporeal membrane oxygenation (ECMO). Furthermore, among the 12 studies analyzed, five studies reported an increased long-term neurologically intact survival with the use of ECPR, four of which were OHCA, 32,34,37,39 while one evaluated ECPR in IHCA 35 (Table 3 in Supplemental Material shows the studies' design, objectives, interventions, outcomes, and results with neurological outcomes. )…”
Section: Quality Assessmentmentioning
confidence: 99%
“…47 While our literature review evaluated the criteria under which ECPR should be performed, four studies reported the need to evaluate CA patients for eligibility to see if they fit for ECPR therapy. 35,39,41,42 These studies report higher survival associated with carefully selected patients after meeting inclusion criteria. 39 These results are significant as they demonstrate the need to make early patient selection conceivable and necessary prior to ECPR therapy.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…In this issue of Emergency Medicine Australasia , Iwashita et al . performed an audit of in‐hospital cardiac arrests that occurred in the Auckland City Hospital ED to determine the potential number of eligible patients for ECPR based on theoretical inclusion criteria 22 . A total of 65 patients were identified to have had an in‐hospital cardiac arrest within the ED, of which seven would be eligible for ECPR.…”
mentioning
confidence: 99%